Acute Neck Trauma in Emergency Medicine: Evidence-Based Assessment, Airway Protection, and Cervical Spine Management - Aldhilan, Ahmed D.; Hani Saad Alanazi,; Layla Ibrahim Maes,; Faisal Khaled Marzouq Al-Mutairi,; Abduljallil Ali Hassan Alabbad,; Nazih Khalil Ghalfan Kamili,; Mahzary Othman Mohammed A,; Wejdan Mohammed Althurwi,; Ahmed Wanas Muhawish Alanazi,; Mohammed Mansour Alsaif,; Abdalaziz Alsaab,; Zakaria Yahya Hussin Najmi,; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Neck trauma is a high-risk emergency presentation due to the concentration of vital vascular, aerodigestive, and neurologic structures within a confined anatomical space. Even minor external injuries can conceal life-threatening internal damage, making timely diagnosis and intervention critical. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> To review evidence-based strategies for assessment, airway protection, and cervical spine management in acute neck trauma, emphasizing zone-based anatomy and mechanism-specific considerations. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A comprehensive literature synthesis was conducted, integrating current guidelines, epidemiologic data, and clinical decision frameworks such as ATLS principles and NEXUS criteria. The review addresses diagnostic imaging modalities, physical examination priorities, and multidisciplinary management pathways. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Neck trauma accounts for 5–10% of trauma cases but carries disproportionate morbidity and mortality. Zone I injuries exhibit the highest lethality due to great vessel involvement and limited surgical access, while Zone II injuries are most common and more accessible for operative intervention. Computed tomography angiography (CTA) has emerged as the preferred initial imaging modality for vascular assessment. Airway compromise remains the foremost threat, often evolving rapidly; early airway control and hemorrhage management are essential. Selective rather than mandatory surgical exploration is increasingly favored, guided by hard and soft signs, imaging, and hemodynamic stability. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Optimal outcomes require early airway protection, vigilant reassessment, and multidisciplinary coordination. Advances in imaging and selective intervention strategies have improved safety, but delayed recognition of esophageal or vascular injury remains a major cause of morbidity and mortality.